Anisotropic thermal transport in phosphorene: effects of crystal orientation. Issue 24 (28th June 2015) - Liu, Te-Huan; Chang, Chien-Cheng
<x xml:space="preserve">Abstract</x> The thermal conductivity of phosphorene is a smooth monotonic decreasing function of the crystal chirality, which exhibits sinusoidal behavior between 0° and 90°.